(3GdVeGfGJ GdOhdjI ddeMGceI GdYGOdI hGdefUaI hehba GdbGfhf GdeUQi efgG (B/ s - (3GTQa eMehO eMeO eMahX s; (3UdGM GdOjf eMehO ahRi YGeQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JgOa gPI GdOQGSI Gdi eMGhdI JCSjS GWGQ eYQai bGfhfi ddeMGceI GdYGOdI hGdefUaI ai VhA GMcGe GdbGfhf GdOhdi GdYGe hGGdbGfhf GdeUQi hef NdGd JLejY hJMdjd eHGOF hbhGYO hTQhW GdeMGceI GdYGOdI hGdefUaI GdeJfGKQI ai GdYOjO ef GdehGKjb GdOhdjI hGdGbdjejI GdeYfjI HMbhb GdGfSGf GdeUOb YdjgG ef bHd GdMcheI GdeUQjI hebGQfJgG HGdbhGfjf GdeUQjI hPdc ef NdGd GdGQcGf GdGQHYI GdJi JTcd ai eVehfgG VeGfGJ GdeMGceI GdYGOdI hGdefUaI hgPg GdGQcGf gi VeGfGJ GdegJe bHd hGKfGA GdeMGceI hVeGfGJ GdSdWI GdbVGFjI hVeGfGJ GdfjGHI GdYGeI hVeGfGJ Mb GdOaGYs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B347-365s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdVeGfGJ GdOhdjIs; (3GdbGfhf GdeUQis; (3GdeMGceI GdYGOdIs; (3VeGfGJ CYVGA GdfjGHI GdYGeI GdOhdjIs; (3VeGfGJ GdSdWI GdbVGFjI GdOhdjIs; (3Mb GdOaGYs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs